2023
DOI: 10.3390/antiox12061263
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites Profiling and Bioassays Reveal Bassia indica Ethanol Extract Protective Effect against Stomach Ulcers Development via HMGB1/TLR-4/NF-κB Pathway

Abstract: Clinical manifestation of gastric ulcers is frequent, in addition to their costly drug regimens, warranting the development of novel drugs at lower costs. Although Bassia indica is well characterized for its anti-inflammatory and antioxidant potential, capacity of its ethanol extract (BIEE) to prevent stomach ulcers’ progression has not been reported. A nuclear protein termed high-mobility group box 1 (HMGB1) plays a key role in the formation of stomach ulcers by triggering a number of inflammatory responses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
0
0
Order By: Relevance
“…: Kochia indica Wight] belongs to the family Amaranthaceae [9]. This family includes a large number of halophytes that are well-known for their therapeutic applications in traditional medical systems and are used for infected skin wounds, internal worms, fungal infections, renal and rheumatic disorders [10] as a cardiotonic [11], anti-inflammatory, and antioxidant [12]. B. indica is an annual herb found in Egypt, India, Pakistan, Northern Africa, Saudi Arabia, and other countries [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…: Kochia indica Wight] belongs to the family Amaranthaceae [9]. This family includes a large number of halophytes that are well-known for their therapeutic applications in traditional medical systems and are used for infected skin wounds, internal worms, fungal infections, renal and rheumatic disorders [10] as a cardiotonic [11], anti-inflammatory, and antioxidant [12]. B. indica is an annual herb found in Egypt, India, Pakistan, Northern Africa, Saudi Arabia, and other countries [13].…”
Section: Introductionmentioning
confidence: 99%
“…The plant extracts are reported to have therapeutically important metabolites including polyphenols, sterols, alkaloids, glycosides, tannins, coumarins, terpenes, and saponins [14]. Moreover, it has been reported that this plant exhibits anti-inflammatory, anticancer [15], antioxidant [16], antimicrobial [17], antifungal [18], antiparasitic [14], anti-ulcer [12], and neuroprotective activities [19].…”
Section: Introductionmentioning
confidence: 99%